2012
DOI: 10.1016/j.celrep.2012.02.007
|View full text |Cite|
|
Sign up to set email alerts
|

PI3K-Akt-mTORC1-S6K1/2 Axis Controls Th17 Differentiation by Regulating Gfi1 Expression and Nuclear Translocation of RORγ

Abstract: The PI3K-Akt-mTORC1 axis contributes to the activation, survival, and proliferation of CD4(+) T cells upon stimulation through TCR and CD28. Here, we demonstrate that the suppression of this axis by deletion of p85α or PI3K/mTORC1 inhibitors as well as T cell-specific deletion of raptor, an essential component of mTORC1, impairs Th17 differentiation in vitro and in vivo in a S6K1/2-dependent fashion. Inhibition of PI3K-Akt-mTORC1-S6K1 axis impairs the downregulation of Gfi1, a negative regulator of Th17 differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
295
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(313 citation statements)
references
References 48 publications
17
295
1
Order By: Relevance
“…Indeed, various drugs, leading to PI3K/Akt inhibition and Foxo1 activation, strongly decreased IL-17A-expressing CD4 T cells during in vitro differentiation of CD4 naive T cells into Th17 cells. These results are consistent with previous studies having shown that the PI3K/Akt/mTORC1 axis is important for Th17 differentiation (52,53). Our results also showed that this regulation of PI3K/Akt inhibitors on Th17 differentiation clearly occurs at the transcriptional level and that it can impact various Th17 genes simultaneously, as shown in this work for il-17a and il-17f genes (see Fig.…”
Section: Pharmacological Modulation Of Foxo1 Activity Controls Th17 Dsupporting
confidence: 82%
“…Indeed, various drugs, leading to PI3K/Akt inhibition and Foxo1 activation, strongly decreased IL-17A-expressing CD4 T cells during in vitro differentiation of CD4 naive T cells into Th17 cells. These results are consistent with previous studies having shown that the PI3K/Akt/mTORC1 axis is important for Th17 differentiation (52,53). Our results also showed that this regulation of PI3K/Akt inhibitors on Th17 differentiation clearly occurs at the transcriptional level and that it can impact various Th17 genes simultaneously, as shown in this work for il-17a and il-17f genes (see Fig.…”
Section: Pharmacological Modulation Of Foxo1 Activity Controls Th17 Dsupporting
confidence: 82%
“…Thymic subsets based on CD4 and CD8 staining were similar between WT and Raptor-T-KO mice ( Fig. 2A), which is consistent with previous observations in Raptor f/fLckCre mice (19). Raptor protein level was obviously decreased in Raptor-T-KO thymocytes (Fig.…”
Section: Significancesupporting
confidence: 81%
“…Interestingly, mTORC1 has been demonstrated to control nuclear localization of multiple molecules both positively and negatively. It inhibits Lipin1 (a phosphatase for phosphatidic acid) and transcription factor EB nuclear translocation (36)(37)(38) but promotes RAR-related orphan receptor-γt nuclear accumulation (19). mTOR itself dynamically shuttles between the nucleus and cytoplasm in a rapamycin-dependent manner (39,40).…”
Section: Significancementioning
confidence: 99%
“…The PI3K/AKT pathway has been associated with Th17 cell development (38) and with IL-17 expression by CCR6 + human memory T cells (39). Thus, targeting MAPK/ERK along with the JAK/ PI3K/AKT pathways may be beneficial for inhibiting Th17-mediated bone loss.…”
Section: Discussionmentioning
confidence: 99%